A mixed-integer programming-based heuristic for project scheduling with work-content constraints. (2017) - Zimmermann, Adrian
We consider the project scheduling problem in which each project activity has a prescribed work content that must be completed by a so-called work-content resource and the activities' resource usage may change over time. The resource usage must lie within prescribed bounds and cannot be changed for a minimum number of consecutive periods. The amount of resource units used determines the requirements for further resources. The activities must be scheduled such that the project makespan is minimised. For this problem, we devise a mixed-integer programming-based heuristic that schedules the activities iteratively. To improve the resource usage for multiple activities simultaneously, subsets of activities are rescheduled each time the activities' resource usage appears to be inefficient. Our computational results for a standard test set from the literature show that our heuristic outperforms the state-of-the-art method for medium- and large-sized instances, and that for many small-sized instances, optimal solutions are obtained. [Received 30 September 2016; Revised 26 January 2017; Accepted 26 April 2017]